Research emphasis and collaboration in Africa - Pouris, Anastassios; Ho, Yuh-Shan (Scientometrics, 2014)
Scientific co-authorship of African researchers has become a fashionable topic in the recent scientometric literature. Researchers are investigating the effects, modes, dynamics and motives of collaboration in a continental research system which is in an embryonic stage and in different stages of development from country to country. In this article we attempt to provide some additional evidence by examining both patterns of collaboration at country and continental levels and the scientific disciplines emphasised. Our findings indicate that the continent’s research emphasises medical and natural resources disciplines to the detriment of disciplines supporting knowledge based economies and societies. Furthermore, we identify that the collaborative patterns in Africa are substantial higher than in the rest of the world. A number of questions related to research collaboration and its effects are raised.